Ночные шорохи: [роман] / Джудит Макнот - Макнот Джудит (АСТ, 2005)
Экземпляры: ФО-3 (201410) / Инвентарный номер: 50330 / Цена: 50.00 / Сис.шифр: И(англ) / Авт.знак: М 15 / ГРНТИ: 17.82 / ББК: 84(7США)